2000
DOI: 10.1111/j.1752-7325.2000.tb04073.x
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Loss and Need for Extractions in American Indian and Alaska Native Dental Patients

Abstract: Objective: This article reports results of the 1991 Indian Health Service PatientOral Health Survey in the areas of tooth loss and need for tooth extraction. Methods: The survey examined a sample of American Indian and Alaska Native dental patients. Tooth loss and need for tooth extraction are explored for a total of 12,349 individuals aged 18 years and older. Results: Complete tooth loss in patients aged 35 years and older was 1 1 percent; in patients aged 65 years and older, it was 42percent. The mean number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…Factors associated with the loss of one tooth or more were older age (≥35 years), severe periodontitis, higher dental caries and previous dental visit. Higher number of teeth lost has also been associated with older age in other populations 15,17,25,27,[30][31][32] . The association with age ≥35 years may be a result of increasing periodontal attachment loss over time 33 , as attachment loss is higher in older people 16,34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors associated with the loss of one tooth or more were older age (≥35 years), severe periodontitis, higher dental caries and previous dental visit. Higher number of teeth lost has also been associated with older age in other populations 15,17,25,27,[30][31][32] . The association with age ≥35 years may be a result of increasing periodontal attachment loss over time 33 , as attachment loss is higher in older people 16,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Between 1984 and 1991, the rate of people with 20 or more teeth increased. Tooth loss was more severe in subjects with diabetes 17 . Studies on other adult Indian populations showed that mean tooth loss was between 0.4 and 13.7 teeth per person, depending on the age group [18][19][20] .…”
Section: Introductionmentioning
confidence: 88%
“…Quanto ao diabetes, observando-se apenas o dado estatístico não foi encontrada significância, mas ao analisar a indicação de extração, metade dos pacientes que possuíam a doença apresentaram necessidade de exodontia. Tais achados estão de acordo com a literatura 9,12 . Logo, apesar da irrelevância estatística neste estudo e, pautado em dados publicados sobre periodontite na presente população 36 , sugere-se que o diabetes seja investigado em estudos futuros como um possível indicador de risco para a necessidade de exodontia.…”
Section: Característicasunclassified
“…As desigualdades socioeconômicas e culturais, as crenças, o acesso ao atendimento, além da própria percepção individual, contribuem para esta condição e exercem grande influência sobre a decisão de extrair um dente [6][7][8] . Por sua vez, fatores como tabagismo, presença de doenças sistêmicas, nível de escolaridade, renda mensal, faixa etária, sexo, estado civil e raça, são considerados fatores modificativos [9][10][11][12] .…”
Section: Introductionunclassified
“…Tooth loss is an outcome of treatment decision as well as disease. 5 Relatively, a few studies have been done to know the risk indicators associated with tooth loss. Hence, here an attempt is made to evaluate the behavioral characteristics of the adults like beliefs about tooth loss, and utilization of available health services which might be associated with tooth loss.…”
Section: Introductionmentioning
confidence: 99%